PENGEMBANGAN JARINGAN AIR BERSIH PADA SISTEM PENGELOLAAN AIR MINUM (SPAM) DI KECAMATAN PADANG TUALANG DALAM MENINGKATKAN KEBUTUHAN AIR BERSIH - Muhammad Firlyandara; Abdi Sugiarto; Cut Nuraini (Bulletin of Engineering Science, Technology and Industry, 2025)
This study aims to explore the existing conditions and constraints faced in the management and distribution of clean water in Padang Tualang District, and to propose effective development strategies. Using a qualitative approach, this study identified key issues, including limited capacity of the water treatment system, damage to the distribution network, and uneven water quality. Various strategies are proposed, such as increasing the capacity of water treatment plants, repairing and expanding the distribution network, diversifying water sources, and empowering communities. This study provides recommendations to local governments, SPAM managers, and communities to work together to realize a more effective and sustainable clean water management system.